PEMODERASIAN MODAL SOSIAL PADA PENGARUH ORIENTASI ENTREPRENEUR TERHADAP PENINGKATAN KINERJA ORGANISASI (STUDI EMPIRIS PADA UKM DI KOTA SURAKARTA) - Nugroho, Sidiq Permono; Setyawan, Anton Agus (Universitas Muhammadiyah Surakarta, 2015)
This study is an advantageous research of prepositions which require empirical tests. The research highlights the effect of entrepreneurial orientation in determining and maintaining sustainability of a company. A sharper business competition requires a bright and right strategy. The term of strategy is usually refers to something not more than an idea, concept, and formulation process, and sometime is inconsistent to its implementation. In the stage of implementation itself, the strategy changes frequently, very fast then it seems to be deviated from the plan that have been made. In the implementation phase, the discrepancy between strategy and internal factors is a common problem. The social capital is an important internal factor of organization, and its able to moderate the entrepreneurial orientation in affecting the organizational performance. The equation constructed in the study proposition is aimed to observe the effects of entrepreneurial orientation to the organizational performance which is moderated by social capital in terms of structural, relation, and cognitive dimensions. This study utilizes multiple analysis groups, a theoretical framework which is suitable to test the various differences between similar estimation models for the different respondent group. The examination results that according to the measurement, a low Moderation of Social Capital (Structural Dimension, Relational Dimension, and Cognitive Dimension) moderates the effect of Entrepreneurial Orientation to the Organizational Performance. The application of Social Capital (Structural Dimension, Relational Dimension, and Cognitive Dimension) of SME especially in Surakarta is still limited to non-business relationship